Kadar Estrogen dan Munculnya Estrus setelah Pemberian Buserelin (Agonis GnRH) pada Sapi Bali yang Mengalami Anestrus Postpartum Akibat Hipofungsi Ovarium - Suartini, Ni Ketut; Trilaksana, I Gusti Ngurah Bagus; Pemayun, Tjok Gde Oka (Veterinary Science and Medicine Journal, 2013)
Normal 0 false false false EN-US X-NONE X-NONE The purpose of this study was to measure the levels of estrogen and the onset of estrous after administration of B userelin on bali cattle experiencing anestrous postpartum due to ovarian hypofunction. This research used twenty seven bali cattles which were divided evenly into three groups of treatment, namely group-one as control group (P0, without treatment), group-two, receiving a single injection of B userelin at dose of 0.02 mg (P1) and group three, receiving repeated injection of B userelin at dose of 0.02 mg at 24 hours interval (P3). Serum estrogen levels were measured at a time off before estrous, a time of estrous, and five days after the onset of estrous using ELISA method. Data were analyzed using statistical analysis of variance and a Duncan’s Multiple Range Test for a further analysis. The results showed that at the stage of estrous, the estrogen level of P0 was lower significantly (p<0.05) than two others treatments (P1 and P2), but those of P1 and P2 were statistically the same (p>0.05). The onset of estrous on P2 was shorter than those of P1 (p<0.05). It can be concluded that the administration of B userelin can trigger an estrous on Bali cattle that experiencing anestrous postpartum due to ovarian hypofunction and repeated administrations of B userelin can shorten the onset of estrous.
Keywords: cattle, anestrous postpartum, estrogen, Buserelin, ovarium hypofunction